Characteristics of potential concussive events in three elite football tournaments. Issue 4 (22nd July 2019) - Armstrong, Nicholas; Rotundo, Mario; Aubrey, Jason; Tarzi, Christopher; Cusimano, Michael D
Abstract : Objective: Identify patterns in the nature and characteristics of potential concussive events (PCEs) in football. Methods: This study analysed the incidence and characteristics of PCEs that occurred during the 2014 and 2018 Fédération Internationale de Football Association World Cups, and the 2016 UEFA Euro Cup. PCEs were defined as direct head collision incidents resulting in the athlete being unable to immediately resume play for at least 5 sec following impact. Results: A total of 218 incidents were identified in 179 matches (1.22 per match, 36.91 per 1000 hours of exposure). The most common mechanism of PCE was elbow-to-head (28.7%, n=68). The frontal region was the most frequently affected location of impact with 22.8% (n=54). Conclusion: Our study defined the identification, prevalence and nature of PCEs in professional international soccer tournaments. Our findings indicate the different contexts and mechanisms of head contact and contact to different regions of the head can be associated with varying signs of concussion. The results highlight targets for future injury prevention strategies.